THE EFFECT OF PRICE ON THE PURCHASE DECISION OF VIRTUAL GOODS IN ONLINE GAME APPLICATIONS MODERATED BY LIFESTYLE - Machrus, Achmad; Marlena, Novi (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
The research was aims to determine 1) how the impact of prices on purchasing decisions, 2) whether lifestyle strengthens the effect of prices on purchasing decisions virtual goods in online games app. The type of research that is used is quantitative research which uses a sampling technique that is purposive sampling with 115 respondents. The data was collected by distributing questionnaires via a google form. This study uses the data analysis techniques MRA (Moderated Regression Analysis). The results of this study prove that 1) prices have a positive impact on the purchase decision of virtual goods in online games app, 2) lifestyle strengthens the effect of prices on purchase decision virtual goods in online games app.